HISTOLOGICAL STRUCTURE OF EPITHELIAL TISSUE AND ITS CLINICAL SIGNIFICANCE - M.I. Muxammadjonov; M.Sh. Mominov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article is dedicated to the histological structure, morphological features, and clinical significance of epithelial tissue. Epithelial tissue serves as a protective barrier between the external and internal environments of the body and performs essential functions such as secretion, absorption, and excretion. The article analyzes the structure of epithelial cells, their connection to the basal membrane, and their high regenerative capacity, using examples from various organs. Furthermore, the histological mechanisms underlying inflammatory processes, degenerative changes, and tumor development resulting from epithelial tissue dysfunction are discussed. The significance of histological examination and biopsy in early disease detection is emphasized, highlighting the integral relationship between histology and clinical medicine.